The Application of Audio Scripts for Micro Learning Meaning and Purpose in Enhancing Students' Learning Creativity - Sungkono, Sungkono; Ekaputra, Firdiawan (PT Mattawang Mediatama Solution, 2024)
The rapid development of technology has an impact on the rapid exchange of information, including in the world of education. Providing provisions for creativity is needed as an effort to prepare graduate students to face rapid changes. This study aims to examine the effectiveness of the application of audio script micro learning meaning and purpose to improve student creativity. This research is an experimental research with a quantitative approach. This study used a pre-experimental design with one class of research samples. Hypothesis testing in this study used a one sample t-test to test the effectiveness of the application of the audio script for micro-learning the meaning and purpose of effective in increasing student learning creativity. The application of audio scripts in micro-learning courses has a positive impact on student creativity as evidenced by an increase in student creativity by 11.2. The increase in student creativity is reinforced by the results of the one samples t test on student creativity data showing a significance value of 0.00, which means that audio script media can improve student creativity skills. Therefore, in this study it can be concluded that the application of audio scripts of micro learning meaning and purpose is effective in increasing student learning creativity.